2021
DOI: 10.1136/jmedgenet-2020-107404
|View full text |Cite
|
Sign up to set email alerts
|

Improving the clinical interpretation of missense variants in X linked genes using structural analysis

Abstract: BackgroundImproving the clinical interpretation of missense variants can increase the diagnostic yield of genomic testing and lead to personalised management strategies. Currently, due to the imprecision of bioinformatic tools that aim to predict variant pathogenicity, their role in clinical guidelines remains limited. There is a clear need for more accurate prediction algorithms and this study aims to improve performance by harnessing structural biology insights. The focus of this work is missense variants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, no multicollinearity problems were detected between the meta-predictors included and the amino acid prediction scores. Similar approach was used previous studies 38 . Afterwards, after the outlier detection, no extreme value could be detected that would affect the result.…”
Section: Discussionmentioning
confidence: 86%
“…However, no multicollinearity problems were detected between the meta-predictors included and the amino acid prediction scores. Similar approach was used previous studies 38 . Afterwards, after the outlier detection, no extreme value could be detected that would affect the result.…”
Section: Discussionmentioning
confidence: 86%
“…However, no multicollinearity problems were detected between the meta-predictors included and the amino acid prediction scores. A similar approach was used in previous studies [32]. Afterwards, after the outlier detection, no extreme value could be detected that would affect the result.…”
Section: Resultsmentioning
confidence: 96%
“…In-silico pathogenicity classifiers were based on output from MetaSVM and CADD. Recent research suggests that gene-specific thresholds provide better performance for missense variants in a subset of genes (Sallah et al, 2022). MetaSVM has been shown to yield high performance in benchmark studies (Anderson and Lassmann, 2018) although, some investigations showed that it can exaggerate pathogenicity of variants in specific proteins (Zaucha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%